The determinants of household consumption in Malaysia - Mohd Zulkifli, Shaliza Azreen; Suhaimi, Ummi Rasyidah; Badri Shah, Noor Sharida; Muhamad Yusuf, Noor Hafizha (Journal of Islamic, Social, Economics and Development, 2025)
This research attempts to study the determinants of household consumption expenditure in Malaysia using an annual data for 30 years from 1981 to 2021. In order to achieve this, independent variables like household income, government expenditure, inflation rate, interest rate, and education while household consumption as dependent variable are chosen as guideline. Then, this research attempts to identify the existence of long-run relationship between the independent variables with household consumption expenditure in Malaysia. Based on Dynamic Ordinary Least Square (DOLS) framework, tests like correlation, unit root test and cointegration test are conducted to get meaningful results. Household income, government expenditure, inflation, and education are proven to have short-run relationship with household income. However, the most significant independent variable cannot be determined due to no detection of co-integration. Finally, the outcome of the research suggests the model of the study has no long run relationship.